Meal Quality of Entrées That Can Be Sold as Competitive Foods in Schools and Potential Impact of the Proposed USDA Rollbacks - Cohen, Juliana F.W. (Nutrients, 2020)
The Healthy, Hunger-Free Kids Act strengthened competitive food standards (i.e., Smart Snacks), but an exemption allows reimbursable meal entrées that do not meet Smart Snack standards to be sold as “competitive entrées” on the same day they are served in the reimbursable meal, and the following day. Proposed rollbacks would enable these competitive entrées to continue to be sold on a third day, increasing the availability of competitive foods exempt from Smart Snacks standards. This study compared the Healthy Eating Index (HEI) scores of potential competitive entrées alone versus full reimbursable school lunches, and examined the nutritional characteristics of potential competitive entrées. Data were from a national sample of 1108 schools from the School Nutrition and Meal Cost Study. Linear regression models, accounting for school-level and state and district policy characteristics, found that HEI scores of competitive entrées were an average of 30 points lower than HEI scores of reimbursable lunches, with greater differences in small and rural schools. Less than 1% of common potential competitive entrees met Smart Snack standards, primarily due to higher sodium and saturated fat levels. The proposed rollbacks are estimated to potentially add approximately 662 mg of sodium and 3 g of saturated fat over three days (1103 mg sodium and 5 g saturated fat over a week) on average relative to Smart Snacks limits. Instead of increasing opportunities to sell competitive entrées, their sales should be further limited.